Students’ Reluctance to Participate in Writing Tasks: Challenges and Ways out - Bhusal, Anil Prasad (JMC Research Journal, 2021)
Writing is a secondary skill as it requires a lot of training and practice to acquire. It is also important for language students in grades eleven and twelve in Nepal as it is the only means of evaluating students' levels of skills and knowledge of the language. This article is based on the first phase of an exploratory action research project. I discovered that students who were hesitant to engage in writing tasks and attempted to discover why they were hesitant despite the importance of writing tasks in passing board exams. Analysis of students' writings, classroom discussion, focus group discussion, and self-reflection were used to collect the data. After the analysis and interpretation of the data, it was found that students’ lack vocabulary and limited understanding of writing mechanics and organization of ideas in coherent manner discouraged them from being involved in writing tasks in the classroom. Moreover, they were not taught writing systematically and both teacher and students spent less time in the class developing students' writing skills.